Gambaran Stres Pengasuhan Pada Orangtua Dengan Anak Usia Sekolah di Masa Pandemi Covid-19 - Muhamad Yunus; Sri Wahyuni; Oswati Hasanah (Fakultas Keperawatan Universitas Andalas, 2022)
The Covid-19 pandemic changed parenting situations such as accompanying children in the study at home, overseeing the children to avoid spreading the disease, etc. This study aims to identify the description of parenting stress on parents with school-age children during the Covid-19 pandemic. This quantitative research uses a simple descriptive approach. 98 respondents were selected using the cluster sampling technique. Parenting Stress Index Short Form is used as a research measuring tool. The results showed that all parents experienced parenting stress during the Covid-19 pandemic, but mainly at a low level, 63 people (64.3%). Parenting stress at a moderate level was experienced by 34 people (34.7%), and a high level of parenting stress was shared by one person (1.0%). The majority of parenting stress levels are low. Parenting stress, based on the domain, mainly occurs in the parental environment. Parents lack knowledge and experience assisting school-age children to learn from home during the Covid-19 pandemic. It is hoped that parents can and can adapt to system changes that occur during the pandemic to reduce the intensity of parenting stress.